A 101-kilodalton heme-binding protein associated with congo red binding and virulence of Shigella flexneri and enteroinvasive Escherichia coli strains. - Stugard, C E (1989)
The ability of Shigella flexneri to bind Congo red or hemin is associated with virulence. A 101-kilodalton (kDa) protein responsible for this phenotype (Crb+) in S. flexneri was identified by a tetramethylbenzidine staining procedure which detects heme-protein complexes in polyacrylamide gels. Labeling of cell-surface polypeptides with 125I revealed that the 101-kDa heme-binding protein is expressed on the cell surface. Expression of the protein was regulated by growth temperature and was found to be encoded by the large virulence plasmid of S. flexneri. Deletion mutants and a Tn5 insertion mutant which were negative for Congo red binding (Crb-) did not express the 101-kDa protein. Enteroinvasive Escherichia coli strains that were Crb+, and whose plasmids shared homology with the S. flexneri virulence plasmid, also expressed the 101-kDa protein. Expression of the protein in S. flexneri and enteroinvasive E. coli correlated with the presence of a 9.2-kilobase EcoRI fragment of these plasmids.